2021
DOI: 10.1155/2021/1007366
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota, Prostatitis, and Fertility: Bacterial Diversity as a Possible Health Ally

Abstract: Background. In health, microorganisms have been associated with the disease, although the current knowledge shows that the microbiota present in various anatomical sites is associated with multiple benefits. Objective. This study aimed to evaluate and compare the genitourinary microbiota of chronic prostatitis symptoms patients and fertile men. Materials and Methods. In this preliminary study, ten volunteers have included 5 volunteers with symptoms of chronic prostatitis (prostatitis group) and five fertile vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 34 publications
0
28
0
6
Order By: Relevance
“…23,51,70 IL2 concentration in SP has been investigated in a total of 768 participants in 19 studies published between 1993 and 2021 (Table 1). 16,21,23,34,36,37,49,51,55,56,[58][59][60][66][67][68][69][70][71] Most studies used either ELISA-based technology (eight of 19 studies) or multiplex microbead-based assays (eight of 19 studies) for quantification.…”
Section: Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,51,70 IL2 concentration in SP has been investigated in a total of 768 participants in 19 studies published between 1993 and 2021 (Table 1). 16,21,23,34,36,37,49,51,55,56,[58][59][60][66][67][68][69][70][71] Most studies used either ELISA-based technology (eight of 19 studies) or multiplex microbead-based assays (eight of 19 studies) for quantification.…”
Section: Ilsmentioning
confidence: 99%
“…53,[55][56][57][58][59][60][63][64][65][66][67][68] Several methodologies have been utilised including ELISA (36 of 64 studies), multiplex microbead-based assays (14 of 64 studies) and the Immulite 2000 automated chemiluminescence immunoassay analyser (seven of 64 studies) (Figure2D). There was a moderate level of TA B L E 3…”
mentioning
confidence: 99%
“… Lactobacillus, Staphylococcus, Bacillus, Faecalibacterium, Listeria, Enhydrobacter, Pseudomonas, Neisseria, Phascolarctobacterium, Dolosigranulum, Haemophilus, [Ruminococcus] torques, Bamesiella, Finegoldia, Prevotellaceae NK3B31 group found in relative abundance in BPH Cross-sectional study, no α-diversity, voided urine only CP/CPPS Shoskes et al (2016) 20 25 CP/CPPS and 25 controls Urine DNA 16S rRNA gene sequencing 17 taxa over-represented in CP/CPPS including Clostridia and Bacteroidia and 5 under-represented including Bacilli , with increased overall bacterial diversity vs. control. Cross-sectional design Mändar et al (2017) 21 21 CP/CPPS and 46 controls Seminal fluid DNA 16S rRNA gene sequencing CP/CPPS group: more Proteobacteria less Lactobacilli (especially Lactobacillus iners ) Lifestyle confounding factors not considered Choi et al (2020) 22 17 CP/CPPS and 4 controls Seminal fluid Bacterial culture and DNA pyrosequencing CP/CPPS group: more Achromobacter, Stenotrophomonas, Brevibacillus Small sample, contaminants not controlled Suarez et al (2021) 2 5 men with CP/CPPS and 5 controls Urine seminal fluid Sequencing and Nitric oxide levels and proinflammatory cytokines in seminal and serum The microbiota present in the semen and urine Samples of fertile men presents more operational taxonomical units. Less microbial diversity could be associated with CP symptoms.…”
Section: Microbiomes Of Urologic Diseasementioning
confidence: 99%
“… 18 Although there are overlapping symptoms between CP/CPPS and bacterial prostatitis or sexually transmitted infections, the presence and type of bacteria on conventional culture did not correlate with the presence or severity of CP/CPPS. 19 Several studies have evaluated the diversity of microbiome in patients with CP/CPPS patients in comparison with that of controls 2 , 11 , 17 , 20 , 21 , 22 , 23 and found that bacterial species are increased in the urine or seminal fluids of patients with CP/CPPS, although definitive patterns are lacking. Elevations of multiple bacterial taxa including Clostridia and Bacteroidia 20 in urine and Achromobacter, Stenotrophomonas, and Brevibacillus 22 in seminal fluids have been identified in patients of CP/CPPS, whereas levels of Lactobacilli are decreased in patients with CP/CPPS.…”
Section: Microbiomes Of Urologic Diseasementioning
confidence: 99%
See 1 more Smart Citation